The Problems of the COVID-19 Pandemic in Higher Education - Salakhova, Valentina B.; Shukshina, Liudmila V.; Belyakova, Natalia V.; Kidinov, Alexey V.; Morozova, Natalia S.; Osipova, Natalia V. (Frontiers in Education, 2022)
Since the outbreak of the pandemic COVID-19, many studies have been conducted to examine how education has responded to the challenges of a completely new situation that has led to the spread of distance education as the only form of instruction. In this study, data were collected and analyzed to understand the difficulties of distance education that higher education students faced during the pandemic. Our goal was to present the results of a socio-psychological study of accessibility, educational resources, applications, and distance learning technologies. A total of 160 students from different Moscow universities participated in the study. A qualitative research method was used for the study. For this purpose, mainly in-depth interviews were conducted to find out the participants’ views on distance education. The data obtained were analyzed by the researchers using qualitative analysis methods. The results showed that all students faced technical difficulties during distance learning, such as poor internet connection, lack of access to online platforms due to the high number of users, lack of necessary equipment, and individual space for online learning. The results also showed low technical readiness for distance education and low quality of online resources, as well as cyber threats during online courses. In addition, the results showed that most students indicated that they would prefer a hybrid form of instruction that combines distance and face-to-face instruction. Implications for further studies are drawn in the conclusion.